Description of Pristina armata n. sp. (Clitellata: Naididae: Pristininae) from a carnivorous plant (Nepenthes sp.) in Borneo, Indonesia - Schenková, Jana (Zootaxa, 2013)
A new clitellate species of Pristininae (Naididae), Pristina armata n. sp., found in the pitcher of the carnivorous plant Nepenthes sp., is reported from East Kalimantan, Indonesia. P. armata n. sp. is a very small clitellate, less than 1 mm long in fixed state, and without proboscis on the prostomium. Signs of reproduction by paratomy were observed, but the generic placement remains preliminary because sexually mature individuals were not found. P. armata n. sp. is characterized by giant hook-like dorsal chaetae at IV. The description of P. armata n. sp. was based on six fixed specimens of different size and stage of development. Noteworthy is the habitat of P. armata n. sp. in Nepenthes pitchers, this being the first clitellate species described from such a habitat. P. armata n. sp. may be a member of the nepenthebionts’ community, realizing its life cycle inside the digestive fluid of the Nepenthes pitcher, or it belongs to nepenthephiles, species that commonly occur in this habitat but do not specialize on it.